SHARIA ECONOMIC LAW ON LEGAL PROTECTION IN MIXED RICE TRANSACTIONS IN PALOLO DISTRICT - Cahaya, Yunika; Oktafian, Mohamad; Ruslan, Murniati (Tadayun: Jurnal Hukum Ekonomi Syariah, 2024)
This research examines the practice of rice blending at Tiga Putri Enterprises, which does not fully follow the principles of transparency stipulated in sharia economic law and consumer protection law in Indonesia. Without notice to consumers, this practice can be categorized as tadlis or fraud under sharia law, which obscures product quality and creates the potential for consumer dissatisfaction or loss. This study used an interview method to explore consumer perceptions regarding product information and business responsibility in delivering quality goods. The results show that the lack of information transparency makes consumers less aware of product quality, resulting in a decline in trust. The implications of the study highlight the importance of regulation and education on transparency in the buying and selling of rice, in order to build a fairer and more responsible trading environment in accordance with sharia principles and consumer protection in Indonesia. Abstrak Penelitian ini meneliti praktik pencampuran beras di Usaha Tiga Putri yang tidak sepenuhnya mengikuti prinsip transparansi yang diatur dalam hukum ekonomi syariah dan hukum perlindungan konsumen di Indonesia. Tanpa adanya pemberitahuan kepada konsumen, praktik ini dapat dikategorikan sebagai tadlis atau penipuan menurut hukum syariah, yang mengaburkan kualitas produk dan menimbulkan potensi ketidakpuasan atau kerugian bagi konsumen. Studi ini menggunakan metode wawancara untuk menggali persepsi konsumen terkait informasi produk dan tanggung jawab usaha dalam penyampaian kualitas barang. Hasil penelitian menunjukkan bahwa kurangnya transparansi informasi membuat konsumen kurang memahami kualitas produk, sehingga terjadi penurunan kepercayaan. Implikasi penelitian menyoroti pentingnya regulasi dan edukasi transparansi dalam jual beli beras, demi membangun lingkungan perdagangan yang lebih adil serta bertanggung jawab sesuai prinsip syariah dan perlindungan konsumen di Indonesia.